Aspek Hukum Customer Dispute Resolution dalam Pengembalian Dana Keterlambatan Penerbangan Berdasarkan Mekanisme Kontrak dan Regulasi - Dikha Anugrah; Bias Lintang Dialog; Anthon Fathanudien; Sri Mulyani (Universitas Kristen Satya Wacana, 2025)
Abstract This study examines the legal aspects of Customer Dispute Resolution (CDR) for refund claims arising from flight delays by framing refunds as a legal consequence of breach of contract under air transportation agreements. The principal legal issues addressed are the conflict between standard airline contractual clauses and the regulatory framework under the Minister of Transportation Regulation No. 89 of 2015, as well as the binding force of the CDR mechanism in ensuring the fulfilment of consumer rights. This research employs a normative legal methodology, drawing on statutory and conceptual approaches. The findings demonstrate that refunds constitute a legal entitlement of consumers resulting from the carrier's non-performance, and therefore cannot be treated as a discretionary corporate policy. However, in practice, a normative disharmony persists between contractual provisions and regulatory standards, which weakens consumer protection. Furthermore, the institutional design of CDR lacks sufficient binding and enforceable force, rendering dispute resolution largely dependent on airlines' voluntary compliance. This study underscores the need to harmonize contractual norms with regulatory mandates and to strengthen the binding character of CDR mechanisms to ensure legal certainty and contractual fairness in air transportation agreements.